Detection of aortic valve from echocardiography in real-time using convolutional neural network - Nizar M.H.B.A.; Chan C.K.; Yusof A.K.M.; Khalil A.; Lai K.W. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus